Planificación Ambiental Turística para el Uso Sostenible del Área Marina Protegida Refugio de Fauna “Santa María” Villa Clara, Cuba - Triana Cabrera, Marlen (Universidad Central "Marta Abreu" de Las Villas, 2009)
The Sabana - Camaguey Archipelago is planned to become the second largest conventional tourism site in Cuba, along with a tourism based on Cuban nature. In the other hand it is considered as an area to be developed in a sustainable way. The Biosphere Reserve “Buena Vista” situated inside of it includes the marine protected area called Refugio de Fauna Santa Maria. Taking into account the importance of Santa María key due to its biodiversity and natural process that took place on it, the accelerated tourism development and the lack of an environmental model to order this area, we are proposing to make the touristic planning to allow a sustainable use of cultural and natural patrimony. Eleven striking actions were identified most of them with incidence over the analyzed habitats; 14 species of fauna, 6 species of flora, 8 fauna assembling, 4 flora assembling, 11 ecosystem and 5 sites were considered as attractive for the tourism. As a support attractive we defined 9 touristic services that the area can offer supported by 6 types of infrastructure, which, together with other infrastructures facilities will allow making a proper use of the area, to protect the natural resources and the visitors as well. The functional zonification resulted in 11 zones, 4 as a conservation zones, 3 as an extensive public use, 3 as an intensive public use, and one socio-administrative. The diversity of the proposal activities to develop in different places should favor the touristic demand of the area. The proposal is the base to set the touristic value of the identified attractive, which conduce to the conception of touristic product of the marine protected area: Refugio de Fauna “Santa María”, established on the acknowledgement of its natural and cultural values.

El Archipiélago Sabana-Camagüey se planifica para ser el segundo polo turístico de sol y playa, junto con el turismo basado en la naturaleza en Cuba. Por otra parte, es considerado como área para el desarrollo sostenible y dentro de sus límites se ubica la Reserva de la Biosfera “Buena Vista”. Una de las zonas núcleos de esta reserva es el Área Marina Protegida Refugio de Fauna “Santa María”, considerada por su elevada biodiversidad y eventos que allí ocurren. Teniendo en cuenta el acelerado desarrollo turístico de cayo Santa María, las afectaciones a sus recursos naturales y la inexistencia de un modelo de ordenamiento ambiental para esta zona, nos propusimos realizar el planeamiento que permita el uso sostenible de su patrimonio natural y cultural. Se identificaron 11 acciones impactantes que inciden en su mayoría en los diez hábitat analizados. Se consideran atractivos turísticos 14 especies de la fauna y seis de la flora, ocho ensamblajes de la fauna y cuatro de la flora, once ecosistemas y cinco sitios. Como atractivos de apoyo, se definieron nueve servicios turísticos, facilitados por seis instalaciones, que junto a otras facilidades de infraestructura permitirán hacer un adecuado uso del área. La zonificación funcional resultó en el límite de 11 zonas, de ellas cuatro zonas de conservación, tres zonas para el uso público extensivo, tres para el uso público intensivo, y una zona socio-administrativa. La diversidad de actividades propuestas a desarrollar en diversos escenarios debe favorecer la demanda turística del área. Una correcta planificación ambiental turística, fundada en el reconocimiento de los valores naturales y culturales, mejorará las posibilidades de conservación de la biodiversidad y asegurara la disponibilidad de sitios y atractivos para la propia actividad turística.
Keywords: Archipiélago Sabana-Camagüey; Reserva de la Biosfera “Buena Vista”; Área Marina Protegida Refugio de Fauna “Santa María”; Reservas Naturales; Natural Reservations; Reserva Marina; Marine Conservation Area; Protección Ambiental; Environmental Protection; Ecosistema; Ecosystem